The impact of urbanization on environmental degradation in Jakarta - Putra, Anggi Aran; Trisnawati, Cahyani Eko; Widayat, Puji Wahyu (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: The urbanization discussed in this paper refers to the process of expansion in the proportion of the population living in urban areas. Urbanization is one of the population-growth processes that drives a region's functional transition from rural to urban activities. The case discussed in this paper is urbanization occurring in Jakarta city. This paper aims to examine the relationship between urbanization and the decline in environmental quality. Methods: In assessing environmental quality, the reference used follows that set by the Ministry of Environment and Forestry, namely the Environmental Quality Index (EQI), which consists of three elements, namely the Water Quality Index (WQI), Air Quality Index (AQI) and Land Cover Quality Index (LCQI). The data collection method used is secondary data collection through a literature review and official data sources from related stakeholders. The collected data is then descriptively analyzed to determine how urbanization affects each variable. Findings: Based on the literature review and the results of the LCQI data used, there is a negative correlation between population growth and land cover in Jakarta. This condition is marked by an increase in floods and an increase in surface temperature. Regarding air quality, this paper found a negative correlation between urbanization and AQI. However, from 2013 to 2018, a positive correlation was found between the population and AQI. Conclusion: This indicates that an increase in population is not always followed by a decrease in environmental quality. Meanwhile, concerning water quality, population growth from the urbanization process significantly impacts water quality in Jakarta. Novelty/Originality of this article: The development of a sophisticated and comprehensive correlation analysis method between population growth and environmental quality indicators provides a predictive tool that city governments can use to monitor, manage, and plan mitigation strategies, as well as support data-driven decision-making in sustainable urban planning.